Bibliometric Analysis of the Search for Cultural Identity in the Phenomenon of Globalization - Farida Arinie Soelistianto; Loso Judijanto; Eva Yuniarti Utami (Westscience Press, 2024)
In an era marked by globalization's far-reaching influence, the exploration of cultural identity within this phenomenon emerges as a critical endeavor. This study undertakes a comprehensive bibliometric analysis to map and analyze the scholarly discourse surrounding the search for cultural identity amidst globalization. Drawing from a vast array of academic literature spanning disciplines such as anthropology, sociology, cultural studies, and communication studies, this research seeks to elucidate key themes, influential works, and emerging trends in the field. Through quantitative analysis of bibliographic data, including publication trends, citation metrics, and authorship patterns, combined with qualitative synthesis techniques, this study aims to offer insights into the complex interplay between globalization and cultural identity. The findings contribute to a deeper understanding of this critical phenomenon and provide a valuable resource for scholars, policymakers, and practitioners interested in comprehending the intricate dynamics of cultural identity in an increasingly interconnected world.